2018
DOI: 10.7717/peerj.4488
|View full text |Cite
|
Sign up to set email alerts
|

The use of nutritional supplements to induce ketosis and reduce symptoms associated with keto-induction: a narrative review

Abstract: BackgroundAdaptation to a ketogenic diet (keto-induction) can cause unpleasant symptoms, and this can reduce tolerability of the diet. Several methods have been suggested as useful for encouraging entry into nutritional ketosis (NK) and reducing symptoms of keto-induction. This paper reviews the scientific literature on the effects of these methods on time-to-NK and on symptoms during the keto-induction phase.MethodsPubMed, Science Direct, CINAHL, MEDLINE, Alt Health Watch, Food Science Source and EBSCO Psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 98 publications
2
41
0
Order By: Relevance
“…In a physiological state of ketosis as during fasting, thanks to the considerable consumption of ketones by the CNS and the balance between insulin and glucagon, ketonemia reaches maximum levels of 7-8 mmol/L [26], with no change in the pH of the blood. During a LCKD the levels of KBs are usually between 0.5-0.6 and 4 [54][55][56] and a nutritional ketosis could be defined as a blood ketones > 0.5 mmol/L [57][58][59][60][61] Indeed, our subjects showed an steep increase in blood BHB during the first 6 days reaching, at the end of the first week 0.55 ± 0.27 mmol/L BHB, whilst the mean value from day 7 to day 84 was 1.77 ± 0.55 BHB. It is therefore essential to make a clear distinction between physiological ketosis (KD, fasting) and a pathological ketosis, such as that which can occur in diabetes when hyperglycemia and insulin deficiency cause uncontrolled rates of KBs and the ketonemia may exceed 20 mmol/L, exposing to the risk of severe acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a physiological state of ketosis as during fasting, thanks to the considerable consumption of ketones by the CNS and the balance between insulin and glucagon, ketonemia reaches maximum levels of 7-8 mmol/L [26], with no change in the pH of the blood. During a LCKD the levels of KBs are usually between 0.5-0.6 and 4 [54][55][56] and a nutritional ketosis could be defined as a blood ketones > 0.5 mmol/L [57][58][59][60][61] Indeed, our subjects showed an steep increase in blood BHB during the first 6 days reaching, at the end of the first week 0.55 ± 0.27 mmol/L BHB, whilst the mean value from day 7 to day 84 was 1.77 ± 0.55 BHB. It is therefore essential to make a clear distinction between physiological ketosis (KD, fasting) and a pathological ketosis, such as that which can occur in diabetes when hyperglycemia and insulin deficiency cause uncontrolled rates of KBs and the ketonemia may exceed 20 mmol/L, exposing to the risk of severe acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Very low carbohydrate diets (ketogenic diets), with fewer than 50 g of carbohydrate per day, have been linked to weight loss and specific health benefits including neurological disorders. Adaptations to a ketogenic diet is often difficult and nutritional aids have been shown to be useful for entering into nutritional ketosis [ 32 ]. A recently concluded study indicated that both low-fat and low-carb diets can work for weight loss, and that there is no “best diet” when it comes to low-carb vs. low-fat diets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, "Flu KD" is neither a MeSh term nor a keyword related with this area of research. Symptoms of keto-induction were reported two decades ago (11), referred to in mainstream and gray literature as "keto-flu, " but these were not well-described in scientific literature (12). In recent years, other than the article by Bostock et al, there have been no publications.…”
Section: Discussionmentioning
confidence: 99%